Employing citizen science to enhance active and healthy ageing in urban environments. (January 2023) - Wood, G.E.R.; Pykett, J.; Banchoff, A.; King, A.C.; Stathi, A.; ,
Abstract: Engaging older residents in problem definition and solution-building is key to the success of place-based initiatives endeavouring to increase the age-friendliness of urban environments. This study employed the Our Voice framework, engaging older adult citizen scientists (n = 14) and community stakeholders (n = 15) across the city of Birmingham, UK. With the aim of identifying urban features impacting age friendliness and co-producing recommendations for improving local urban areas, citizen scientists participated in 12 technology-enabled walkability assessments, three in-person discussion groups, two one-to-one online discussions, and two workshops with community stakeholders. Together, citizen scientists co-produced 12 local and six city-wide recommendations. These recommendations were embedded into an implementation framework based on workshop discussions to identify age-friendly pathways in urban environments. Highlights: Place-based approaches can draw on older residents' expertise to identify and address urban features impacting healthy ageing. Citizen science can engage older adults and stakeholders to co-produce recommendations for mobilizing local and city-wide improvements. An implementation framework, embedded in older resident and stakeholder knowledge, was elicited for promoting scalable age-friendly actions.